MENGEMBANGKAN KELOMPOK MENJAHIT BINTAN BERKARYA MELALUI KERAJINAN TANJAK SEBAGAI WARISAN BUDAYA MELAYU - Pardede, Ranat Mulia; Sihombing, Agustinus; Yanto, Meidi; Syahputra, Ilham Kurniawan; Setiawan, Roni; Malinda, Delsa; Cahayani, Nur Suci; Anugrah, Sentia; Pratiwi, Erica (P3M STIE Pembangunan Tanjungpinang, 2025)
In Ekang Anculai Village, there is a group that manages MSMEs engaged in sewing which are members of a group called